ANALISIS KESALAHAN BERBAHASA SURAT KABAR JAWA POS RADAR SOLO PADA RUBRIK TREVELLING EDISI BULAN JANUARI - MARET TAHUN 2020 - Alfiyani, Candra; Hidayanto, Muhammad Rizki; Saputri, Nindya Kyky Ayu (LPPM STKIP PGRI Bandar Lampung, 2020)
Newspaper is a print media that functions to provide information, which is written according to gifts and language rules (Indonesian language). in this study examines and analyzes language errors in the Jawa Pos Radar Solo newspaper in the January-March edition of the Trevelling rubric in 2020. The type of research used is descriptive descriptive research. the technique used is refer to the one used to obtain data and record it to record the acquisition of data. based on the results of the study found errors in the spelling level language in the form of errors in writing words, mistakes in capital letters, errors in commas, errors in writing numbers, errors in the use of periods and colons, andparticle use error.errors at the level of syntax in the form of morphological manifestations are errors of suffix, perfix errors, and reduplication errors. errors at the level of discourse in the form of misuse of references and errors there are several topics in one paragraph.